The “Reading the Mind in the Eyes” test in autism-spectrum disorders comparison with healthy controls: a systematic review and meta-analysis - Peñuelas Calvo, Maria Inmaculada; Sareen, Aditya; Sevilla-Llewellyn-Jones, Julia; Fernández-Berrocal, Pablo (Springer Nature, 2019)
We conducted a meta-analysis of 18 studies to establish whether a relation exists between Reading the Mind in the Eye Test (RMET) performance and intelligence quotient (IQ) in individuals diagnosed with autism-spectrum disorders (ASD) and controls, taking into account relevant characteristics such as age, gender, and autism quotient. Our findings indicate that RMET performance was better in controls compared with those diagnosed with ASD. We found that RMET performance is dependent on full and verbal IQ and age in controls. However, RMET performance is negatively correlated with performance IQ in individuals diagnosed with ASD. These results suggest that the methodology applied by ASD when taking the RMET is different from control individuals and might depend less on verbal abilities.
Keywords: Autismo; intelligence; Autism-spectrum disorder; Reading the Mind in the Eye Test